The plays of Lillian Hellman, Clifford Odets and William Inge on Slovene stages - Slunjski, Mateja (Acta neophilologica, 2002)
After the Second World War, Slovene theatres started to include in their repertoires more and more American authors and their plays. Their choice were varied, from serious dramas by Eugene O'Neill, Tennessee Williams and Arthur Miller, to comedies by Norman Krasna and John Van Druten dependant mostly on the availability of the texts. In the immediate postwar years the theatres liked to present playwrights with progressive ideas in their plays, such as Lillian Hellman and her "The Little Foxes", which was successfully produced at three Slovene theatres, while her "The Children's Hour" received negative reviews. In the fifties, three theatres chose two plays by Clifford Odets, "Golden Boy" and "Country Girl", mainly because of his socially critical ideas and his admiration of humanity. His plays were rather well received; however, the critics doubted his literary genius. William Inge and his plays, "Come Back, Little Sheba", "Picnic" and "Bus Stop", chosen mainly because of the warmth with which the author depicted the tragedy and the beauty of life, were produced at three Slovene theatres. The author received rather wide-ranging opinions from the critics. Some thought him to be an unoriginal depicter of dull American life, while others praised his lyricism and new dramatic techniques.
Keywords: 20.st.; ameriška dramatika; Hellman, Lillian, 1907-1984; Inge, William, 1913-1973; literarna recepcija; Odets, Clifford, 1906-1963; slovensko gledališče; uprizoritve